Numerical Study of the Flow of Two Radiative Nanofluids with Marangoni Convection Embedded in Porous Medium. (17th January 2022) - Gupta, Ravi; Gaur, Manish; Al-Mdallal, Qasem; Purohit, Sunil Dutt; Suthar, Daya Lal
Abstract : The aim of this study is to investigate the flow of two distinct nanofluids over a stretching surface in a porous medium with Marangoni convection. This investigation is studied under the effect of thermal radiation. Here, we have considered Fe 3 O 4 and ZrO 2 nanosized particles suspended in engine oil (EO) base fluid. For the numerical simulation of the flow, the fourth-order Runge-Kutta method and suitable similarity solutions were used. Numerical solutions with graphical representation are presented. Fe 3 O 4 / EO nanofluid is more significant in the cooling process in comparison to ZrO 2 / EO nanofluid. With increased radiation and temperature ratio parameters, a decrement in the temperature field has been noticed for both nanofluids. For increased values of volume friction parameter, a decrement is noticed for velocity profile and increment is noted for temperature profiles for both nanofluids. Also, a reduced velocity profile can be obtained with increased porosity parameter.